ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA SD NEGERI 54 PONTIANAK - Sulisti, Hidayu; Janah, Roikhatul (Jurnal As Sibyan, 2023)
Mathematical literacy is the ability to understand, use and interpret numbers and mathematical concepts, which is an important skill for every student to be a master. Mathematical literacy is important because it transcends cultural differences and economic inequality. The goal is to see the world through mathematical eyes, and the emphasis is on higher-order thinking, the development and application of general problem-solving skills rather than basic mathematical skills. The approach used in this research is a qualitative approach with a descriptive method. Based on the research results, it was found that students at SD Negeri 54 Pontianak had skills in solving and formulating problems with a high percentage, namely 70%. Students have the skills to explain solutions and interpret conclusions, the percentage is 47.5%. Meanwhile, the aspect of applying mathematical concepts or procedures obtained a percentage of 47.8%.